2021
DOI: 10.48550/arxiv.2112.00822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational constraints on Starobinsky $f(R)$ cosmology from cosmic expansion and structure growth data

Pedro Bessa,
Marcela Campista,
Armando Bernui

Abstract: The unknown physical nature of the Dark Energy motivates in cosmology the study of modifications of the gravity theory at large distances. One of these types of modifications are the theories known as f (R) gravity. In this paper we use observational data to both constraint and test the Starobinsky f (R) model [57], using updated measurements from the dynamics of the expansion of the universe, H(z), and the growth rate of cosmic structures, [f σ8](z), where the distinction between the concordance ΛCDM model an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In particular, it has been found that CC are extremely useful in combination with other cosmological probes (SNe, BAO, CMB) to increase the accuracy on cosmological parameters (such as X k , X m and H 0 , see, e.g., Haridasu et al 2018;Gómez-Valent and Amendola 2018;Lin et al 2021), to determine the time evolution of the dark energy EoS (Moresco et al 2016a;Zhao et al 2017;Di Valentino et al 2020;, and also to provide tighter constraints on the number of existing relativistic species and on the sum of neutrino masses by breaking the existing degeneracies between parameters (Moresco et al 2012b(Moresco et al , 2016a. As suggested by Linder (2017), the measured H(z) data have also been used in combination with the growth rate of cosmic structures to construct a new diagram to disentangle cosmological models (Moresco and Marulli 2017;Basilakos and Nesseris 2017;Bessa et al 2021). Finally, the CC data, in combination with BAO and SNe, have proven to be extremely useful also to test the distanceduality relation and measure the transparency (or equivalently, the opacity) of the Universe (Holanda et al 2013;Santos-da-Costa et al 2015;Chen et al 2016b;Vavryčuk and Kroupa 2020;Bora and Desai 2021;Renzi et al 2021).…”
Section: Comparison With Independent Probesmentioning
confidence: 99%
“…In particular, it has been found that CC are extremely useful in combination with other cosmological probes (SNe, BAO, CMB) to increase the accuracy on cosmological parameters (such as X k , X m and H 0 , see, e.g., Haridasu et al 2018;Gómez-Valent and Amendola 2018;Lin et al 2021), to determine the time evolution of the dark energy EoS (Moresco et al 2016a;Zhao et al 2017;Di Valentino et al 2020;, and also to provide tighter constraints on the number of existing relativistic species and on the sum of neutrino masses by breaking the existing degeneracies between parameters (Moresco et al 2012b(Moresco et al , 2016a. As suggested by Linder (2017), the measured H(z) data have also been used in combination with the growth rate of cosmic structures to construct a new diagram to disentangle cosmological models (Moresco and Marulli 2017;Basilakos and Nesseris 2017;Bessa et al 2021). Finally, the CC data, in combination with BAO and SNe, have proven to be extremely useful also to test the distanceduality relation and measure the transparency (or equivalently, the opacity) of the Universe (Holanda et al 2013;Santos-da-Costa et al 2015;Chen et al 2016b;Vavryčuk and Kroupa 2020;Bora and Desai 2021;Renzi et al 2021).…”
Section: Comparison With Independent Probesmentioning
confidence: 99%
“…The literature reports diverse compilations of measurements of the growth rate of cosmic structures, [ f σ 8 ](z) (see, e.g. [32][33][34]), which we update here. Our compilation of f (z) data, shown in Table 1, follows these criteria:…”
Section: The F (Z) Datamentioning
confidence: 99%
“…In the standard model of cosmology, known as ΛCDM model, the phase of accelerated expansion is caused by a fluid (dark energy) of negative pressure and constant equation of state ω = −1. However, several theories [4][5][6] developed over time are able to reproduce the effects of dark energy, but, still, only with more accurate cosmological observations we will have a definitive answer.…”
Section: Introductionmentioning
confidence: 99%